al 'Alaqah baina al Qalq wa Mahaarah al Kitaabah Laday Thullab al Madrasah al Tsanawiyah al Islamiyah al Hukumiyah 5 Bogor - Septiani, Wulan; Alawiyah, N Lalah; Ridlo, Ubaid (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2025)
This research aims to identify the level of writing anxiety among tenth-grade students at MAN 5 Bogor and its relationship with their writing skills. The study employs a quantitative correlational method, with a sample of 74 students selected through Proportional Random Sampling from a total population of 285 students. Data collection techniques included a writing anxiety questionnaire based on the Second Language Writing Anxiety Inventory (SLWAI) by Cheng, using a Likert scale, as well as interviews and writing tests. The collected data was analyzed using the Product Moment Correlation formula. The results indicate that students’ writing anxiety falls into the "moderate" category, with an average score of 63.62. Correlation analysis revealed that the rxy value was 0.622, which is higher than the critical values at the 5% significance level (0.229) and the 1% significance level (0.298). Accordingly, the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected, confirming a statistically significant relationship between writing anxiety and writing skills. However, the strength of this relationship is classified as "moderate," suggesting that while writing anxiety affects writing skills, it is not the sole determinant of students' writing performance